Elementary School Curriculum Structure in Southeast Asia: A Comparison of the Indonesian and Philippine Education Systems - Vivi Rulviana; Heny Kusuma Widyaningrum; Fida Chasanatun; Dewi Tryanasari; Sri Lestari; Mary Jane L Tomas (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Education in Southeast Asian countries continues to evolve in line with the demands of globalization and the need for competitive human resources. Indonesia and the Philippines are two countries that place significant emphasis on developing basic education as a foundation for developing 21st-century competencies. Indonesia is currently implementing the Independent Curriculum, which emphasizes learning flexibility, differentiated learning, and strengthening student character through the Pancasila Student Profile. Meanwhile, the Philippines implements the K-12 curriculum designed to align the national education system with international standards and prepare graduates for continuing their education and entering the workforce. This study aims to analyze and compare the structure of elementary school curricula in Indonesia and the Philippines, including educational objectives, subject structure, learning load, and competency orientation. The method used is a comparative study with a qualitative approach through an analysis of curriculum policy documents in both countries. The results of the study indicate that although both curricula share the same goal of improving the quality of basic education, there are significant differences in the emphasis on curriculum flexibility, learning approaches, and orientation to learning outcomes. These findings are expected to serve as reflection and reference material in the development of elementary education curriculum policies in the Southeast Asian region.